2018
DOI: 10.3390/su10041286
|View full text |Cite
|
Sign up to set email alerts
|

Infrastructures as Catalysts: Precipitating Uneven Patterns of Development from Large-Scale Infrastructure Investments

Abstract: While infrastructure investments in developing regions may bring about aggregate benefits, the distribution of those benefits cannot be ignored. The present paper examines such distributional effects based on two illustrations: rural roads in Ethiopia and flood control systems in Bangladesh. In both cases, the infrastructures promote particular development patterns towards market-economic transformations and integration. We liken the introduction of these infrastructures to the addition of a catalyst in a chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 49 publications
2
9
1
Order By: Relevance
“…Vehicle ownership is not a limiting factor in the distribution of benefits in the case of agricultural roads in Garut District. This finding is different from the results of a study in Ethiopia [22]. In four villages observed, farmers have not used private vehicles to transport agricultural products.…”
Section: Discussioncontrasting
confidence: 99%
“…Vehicle ownership is not a limiting factor in the distribution of benefits in the case of agricultural roads in Garut District. This finding is different from the results of a study in Ethiopia [22]. In four villages observed, farmers have not used private vehicles to transport agricultural products.…”
Section: Discussioncontrasting
confidence: 99%
“…On the one side, the share of people who favored the road was higher among people in households with fewer adults and higher income. We do not have a clear explanation of why the number adults in a household was associated with a lower probability of favoring the road, but the finding that households with higher income and living in villages with existing road access are more likely to favor the road are in line with the large number of references to the potential economic opportunities offered by the road and with previous works showing that people with stronger links to the market economy seem to be the ones reaping most benefits from the opening of new roads (Angelsen, 2001(Angelsen, , 2012Perz et al, 2010;Rammelt, 2018).…”
Section: Variation In Opinions About the Construction Of The Roadsupporting
confidence: 81%
“…This also means that the links between infrastructure investment and economic growth could be influenced by institutional quality (Okoh and Ebi, 2013). Nevertheless, insufficient attention has been typically paid to the development of the necessary institutions to operate and maintain infrastructures in Ethiopia (Rammelt, 2018).…”
Section: Equitable Infrastructure Allocation In Ethiopian Context: Conceptual/ Empirical Frameworkmentioning
confidence: 99%
“…A review of the literature indicated that there is gradually a consensus that economic development is a multidimensional process that includes interactions between different goals of development and therefore would need systematically designed policies and strategies (Rammelt, 2018;Ashenafi, 2017). Specifically, infrastructure equity issues are complex and multifaceted.…”
Section: Equitable Infrastructure Allocation In Ethiopian Context: Conceptual/ Empirical Frameworkmentioning
confidence: 99%